Is Brain Fog a Temporary or Life-long Condition? - Niknafs, Afshan (International Clinical Neuroscience Journal, 2023)
In the 1880s, German physician Georg Greiner coined the concept of “brain fog” to describe the cognitive deficits associated with delirium. The term “brain fog” has been used intermittently since then to describe sluggish cognition. It gained popularity again in the 1990s as a way to describe chronic fatigue syndrome and some autoimmune diseases. However, there are no diagnostic criteria for brain fog and it is not a medical condition.1 The term “brain fog” describes cognitive difficulties that are increasingly used colloquially. Long-term COVID-19 is characterized by persistent symptoms following a COVID-19 diagnosis that cannot be explained by any other illness. Persistent symptoms following COVID-19 are often described as “brain fog.” Brain fog syndrome, which is associated with excessive academic strain, was revived in the 1960s and was included in the DSM-IV.2 As a result of post-COVID-19 infection, residual cognitive impairment (“brain fog”) often interferes with work and daily activities.3 Recent investigations have shown that fungal co-infections significantly affect the morbidity and mortality of patients with COVID-19.